The Bassanos Venetian musicians and instrument makers in England ; 1531 - 1665 - Lasocki, David 1947- (Scolar Press, 1995)
The second half of the book discusses the family's musical activities. At the English Court the Bassanos made up a recorder consort that lasted 90 years; they also played in the flute/cornett and shawm/sackbut consorts. As instrument makers their fame extended throughout Europe. The book's appendices present information on the Venetian branch of the family and the musical activities of the English branch since 1665